2013
DOI: 10.1371/journal.pone.0073788
|View full text |Cite
|
Sign up to set email alerts
|

Fate Analysis of Adult Hippocampal Progenitors in a Murine Model of Fetal Alcohol Spectrum Disorder (FASD)

Abstract: Prenatal alcohol exposure can lead to fetal alcohol spectrum disorder (FASD) and associated behavioral impairments that may be linked to disruptions in adult hippocampal neurogenesis. Social and physical enrichment has been proposed as a potential therapeutic approach toward reversing behavioral deficits associated with FASD and is also a potent stimulator of adult hippocampal neurogenesis. In the present study, we utilized a genetic fate mapping approach in nestin-CreERT2/YFP bitransgenic mice to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 73 publications
1
45
0
Order By: Relevance
“…While not a part of the present study, previous work with our PAE model has found deficits in neurogenesis [47] increased depressive behavior [48] and learning deficits [36]. Although the existing literature suggests that CDK5 and GSK3β contribute to behavioral and cognitive functioning, their roles in PAE-associated impairments in these processes are unknown.…”
Section: Discussionmentioning
confidence: 69%
“…While not a part of the present study, previous work with our PAE model has found deficits in neurogenesis [47] increased depressive behavior [48] and learning deficits [36]. Although the existing literature suggests that CDK5 and GSK3β contribute to behavioral and cognitive functioning, their roles in PAE-associated impairments in these processes are unknown.…”
Section: Discussionmentioning
confidence: 69%
“…In a similar drinking model of PAE using 10% ( w / v ) ad libitum, with exposure from GD0 to 19 as a low-moderate BAC paradigm study, PAE mice did not respond to an enriched environment with enhanced neuronal progenitor survival or differentiation in the subgranular zone of the dentate gyrus (Choi et al 2005). In a follow-up study using the same PAE paradigm but limiting alcohol exposure to 4 h per day, it was shown that post-mitotic neurons from PAE mice housed in an enriched environment are not capable of survival in the dentate gyrus (Kajimoto et al 2013). Moreover, the neurogenesis deficit was associated with impaired spatial pattern recognition and caused by dentate gyrus-mediated neuronal (learning) impairments in these PAE mice (Kajimoto et al 2013).…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…In a follow-up study using the same PAE paradigm but limiting alcohol exposure to 4 h per day, it was shown that post-mitotic neurons from PAE mice housed in an enriched environment are not capable of survival in the dentate gyrus (Kajimoto et al 2013). Moreover, the neurogenesis deficit was associated with impaired spatial pattern recognition and caused by dentate gyrus-mediated neuronal (learning) impairments in these PAE mice (Kajimoto et al 2013). Thus, while dosage of alcohol in the PAE mouse paradigms discussed might vary, it appears that there are changes in brain morphology and cellular differentiation at any dosage of alcohol exposure, although some cell types are more resilient than others.…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…This “drinking in the dark” model results in blood alcohol content of 20 mM 4 h after consumption, similar to slightly more than one drink per day (Valenzuela, Morton, Diaz, & Topper, 2012); dams consume alcohol chronically, during preconception and gestation up to embryonic (E) days 15–17. Neurogenesis was chosen as a mechanism for investigation based on our previous publications demonstrating that alcohol elicits long-lasting effects seen in adulthood on neural progenitor cells (NPC) left over from development, including alterations in cell fate (Kajimoto, Allan, & Cunningham, 2013) and the neurogenic capacity to respond to environmental cues (Choi, Allan, & Cunningham, 2005). Ex vivo proliferating and differentiated cell cultures comprised of NPC from E15–E17 tissue exposed to alcohol in vivo were used for transcriptome analysis of neurogenesis-related genes.…”
Section: Introductionmentioning
confidence: 99%